DYNAMICS OF DIGITAL MARKETING HR MANAGEMENT AND SUSTAINABLE STRATEGY IN INDONESIA'S DIGITAL ERA BUSINESS: A COMPREHENSIVE REVIEW - Kadeni Kadeni; Zahara Tussoleha Rony; Abdul Rosid; Abdul Wahab Syakhrani; Mohammad Ahmad Bani Amer (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
In the dynamic landscape of Indonesia's digital-era business environment, the management of Human Resources (HR) within digital marketing has become a critical determinant of success. This comprehensive review offers a holistic examination of the intricate dynamics of HR management in the context of digital marketing and the formulation of sustainable strategies tailored to the Indonesian business ecosystem. It combines qualitative and quantitative research methods to explore HR practices, recruitment, education, training, leadership, motivation, retention, and the role of inclusivity and diversity in the workforce. The findings highlight the evolving skill sets and competencies required of HR professionals in the digital age, emphasizing the need for robust recruitment and selection processes. Education and training are pivotal for keeping digital marketing teams competitive and innovative, with leadership playing a key role in guiding teams through the ever-changing digital landscape. Inclusivity and diversity within digital marketing teams are critical for reflecting the diversity of the digital marketplace and generating innovative ideas. Sustainable strategies are essential for ensuring the longevity and success of businesses in the dynamic digital marketplace of Indonesia.